Pengembangan Buku Saku Permainan Montessori Sebagai Alternatif Untuk Mengatasi Gangguan Penerimaan Makan Pada Anak Usia Mpasi - Ramanda, Dhea Puteri; Riska, Nur; Mahdiyah, Mahdiyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to develop a book to help mothers who have children at the age of complementary feeding so that they can find out more information related to child growth and development, types of eating disorders, Montessori education and the importance of motor stimulation in children, and contains games that can help fine motor stimulation in children aged 6-24 months. The research method used is Research and Development (R&D) with the PPE (Planninng, Production, Evaluation) development model by Richey and Klein. This pocket book passed validation from material experts and media experts as well as feasibility tests carried out to the Principal and parents of students at KB TK Semut-Semut The Natural School and mothers who have children at the age of complementary feeding at Posyandu Anggrek 2. The results of this study indicate that the assessment obtained from material experts is in the field of Montessori 93.1% with a very good category, in the field of nutritionists 75% with a good category, and in the field of psychology 95.4% with a very good category. The assessment of media experts was 96.7% with a very good category. The results of the assessment in the user feasibility test include one to one test 75% with a good category, small group test 94.5% with a very good category, and field test 95.7% with a very feasible category. The results of the above research conclude that the book Train Children's Motoric: Games to Help Sensory Aspects at the Age of 6-24 Months is suitable for use as needed.